Confucius - Kaizuka, Shigeki (G. Allen & Unwin, 1956)
An ideal way to discover the teachings of Confucius! Fingarette’s primary aim is to help readers discover what is distinctive in Confucius and to learn what he can teach us. Fingarette—who thinks the best way to discover Confucius’s teaching is by taking him at his word—uses original text as his principal resource in an effort to try to see what it says, what it implies and what it does not say or need not imply.